The Correlation between the Occlusal Vertical Dimension of the Face and the Length of the Index Finger, Thumb, and the Distance from the Distal Angle of the Eye to the Angle of the Mouth (In vivo study) (Latakia University Journal -Medical Sciences Series, 2021)
Aim of study: Attempting to reach a method to measure the vertical dimension of the face with the simplest equipment, with less time, without patient intervention, and by following less complex procedures.Materials and methods: A clinical study was conducted on a sample consisting of 100 patients divided into 25 females and 25 males (with slender jaws), 25 males and 25 females (with complete teeth), where the vertical dimension of the patients represented by the distance from the height of the nose to the height of the chin was measured in addition to measuring the length Index finger, thumb length, the distance between the distal angle of the eye and the mouth angle, for all of these measurements, Farnier digital callipers was used.Results: In females, we noticed a correlation relationship between the occlusal vertical dimension of the face and the three variables. For the males, there was a correlation relationship between the occlusal vertical dimension and the variable distance between the distal angle of the eye and the mouth angle. For the relationship between the occlusal vertical dimension and the length of the index finger Thumb Length, There was no correlation between the variables.Conclusions: It has become possible to rely on the length of the index finger, the length of the thumb, and the distance between the distal angle of the eye and the angle of the mouth as a method used to measure the occlusal vertical dimension of the face in females. In males, the distance between the distal angle of the eye and the mouth angle can be used only as a method for measuring the occlusal vertical dimension of the face.